A comprehensive analysis of the relationship between temperature and species diversity: The case of planktonic foraminifera - Gao, Junfeng; Su, Qiang (Frontiers in Marine Science, 2022)
The relationship between temperature (T) and species diversity is one of the most fundamental issues in marine diversity. Although their relationships have been discussed for many years, how species diversity is related to T remains a controversial question. Previous studies have identified three T - diversity relationships: positive, negative and unimodal. Recently, the unimodal relationship has received great attention. However, these studies may be biased by (1) considering the insufficient T range of database, (2) using a single diversity metric (generally species richness, S), and (3) rarely considering species abundance distribution (SAD) that can better represent diversity. Here, to seek a more comprehensive understanding of T - diversity relationships, their relationships are evaluated according to a global planktonic foraminifera dataset, which is usually considered as a model dataset for exploring diversity pattern. Species diversity are estimated by four most commonly used metrics and a new SAD parameter (p). Results show that S and Shannon’s index support the typical unimodal relationship with T. But evenness and dominance do not have significant unimodality. Additionally, this study conjectures that SAD parameter p with increasing T will gradually approach the minimum 1, noting that SAD (Nr/N1, Nr and N1 is the abundance of the r-th and the first species in descending order) tends to be 1: 1/2: 1/3... . This study suggests that the T - diversity relationship cannot be wholly reflected by S and the other aspects of diversity (especially SAD) should be considered.